2013
DOI: 10.1002/psc.2576
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assembling organo‐peptide bolaphiles with KLK tripeptide head groups display selective antibacterial activity

Abstract: In keeping with recent efforts to generate compounds for antibiotic and microbicide development, we focused on the creation of non-natural organo-peptide hybrids of antimicrobial peptide amides (KLK(L)n KLK-NH2 ) derived from sapecin B and a self-assembling oligoglycine organo-peptide bolaphile containing an ω-amino fatty acid residue. The hybrid organo-peptide bolaphiles with two cationic KLK tripeptide motifs linked with an ω-amino acid residue (penta-, octa- or undecamethylene chain) maintained the self-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Another approach for the design of self-assembling AMPs is to modify the peptides with highly hydrophobic molecules. Usually, short charged oligopeptides or AMPs were used as the peptide moiety to service as the polar head, while fatty acid, cholesterol, Fmoc and other hydrophobic molecules are used for the nonpolar tail [18,19,47,80,83,84]. Micelles and hydrogels are the most common self-assembly forms for this kind of AMPs [18,19,80,83], while other types of self-assembly are also observed [84].…”
Section: Conjugation Of Hydrophobic Moietiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach for the design of self-assembling AMPs is to modify the peptides with highly hydrophobic molecules. Usually, short charged oligopeptides or AMPs were used as the peptide moiety to service as the polar head, while fatty acid, cholesterol, Fmoc and other hydrophobic molecules are used for the nonpolar tail [18,19,47,80,83,84]. Micelles and hydrogels are the most common self-assembly forms for this kind of AMPs [18,19,80,83], while other types of self-assembly are also observed [84].…”
Section: Conjugation Of Hydrophobic Moietiesmentioning
confidence: 99%
“…Usually, short charged oligopeptides or AMPs were used as the peptide moiety to service as the polar head, while fatty acid, cholesterol, Fmoc and other hydrophobic molecules are used for the nonpolar tail . Micelles and hydrogels are the most common self‐assembly forms for this kind of AMPs , while other types of self‐assembly are also observed . Proper peptide sequences, hydrophobic molecules and linkers between the peptides and the hydrophobic moieties could be selected to endow the designed peptide with specific responsiveness, such as pH , ionic strength , redox , light , thermal and enzymatic responsivenesses.…”
Section: Approaches For the Design Of Self‐assembling Ampsmentioning
confidence: 99%
“…165 Organo-peptide bolaphile hybrid systems with an ω-amino acid moiety also formed supramolecular structures like fibres, ribbons and rods. 166,167 It was observed that excess hydrophobicity leads to premature self-assembly of the cationic bolaphiles in aqueous solution. 166 Interestingly, metal ion mediated self-assembly of a short peptide amphiphile (sPA) with a Tyr-Tyr-β-Ala backbone also exhibits a fibre-like morphology.…”
Section: Reviewmentioning
confidence: 99%
“…166,167 It was observed that excess hydrophobicity leads to premature self-assembly of the cationic bolaphiles in aqueous solution. 166 Interestingly, metal ion mediated self-assembly of a short peptide amphiphile (sPA) with a Tyr-Tyr-β-Ala backbone also exhibits a fibre-like morphology. 168 Dutta et al recently reported an m-aminobenzoic acidbased (m-ABA) dipeptide, which self-assembles into amyloid fibril structures.…”
Section: Reviewmentioning
confidence: 99%
“…To search for a template, six AMPs that have never been tested against Salmonella were used in this study, including peptide KLK (KLKLLLLLKLK) and KLK1 (KLKLLL-LLKL) derived from sapecin B of flesh fly (Sarcophaga peregrina) larva [12][13][14][15][16][17], BmKn-2 (FIGAIARLLSKIF), and BmKn-22 (FIGAIARLLSK) derived from scorpion (Buthus martensii Karsch) venom [18][19][20][21][22], and Pug-1 (LLKLFFPFLETGE) and Pug-4 (FPSFLVGR) derived from pomegranate (Punica granatum L.) fruit [23]. The peptides were screened for their antibacterial potential against Salmonella using the broth microdilution method (as detailed in Section 2.4.1).…”
Section: Selection Of a Peptide-templatementioning
confidence: 99%